PERJANJIAN PETANI PENGGARAP DENGAN PEMILIK LAHAN DAN PENDEREP PADI PERSPEKTIF HUKUM EKONOMI SYARIAH - Purbatin Fuad Achmadi (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2018)
The form of cultivate farmers' agreement with the owners and the harvesters of rice based on the customary law which up to now has tended to be detrimental to cultivate farmers in the village of Kejawar, Banyumas. For that reason, the perspective of sharia economic law seeks to provide new breakthroughs so that the agreements or contracts can provide benefits and expediency to all parties.Basically, the form of cultivate farmers' agreement with the owners and the harvesters of rice field is divided into two agreements:1. Agreement between the rice field owners and cultivators of rice fields. 2. Agreement between the paddy field cultivators with the harvesters, or sometimes agreements among the paddy field cultivators and rice field harvesters who involve or seek approval from the rice field owners.The writer tries to solve the problem with a cooperation contract in a business or partnership (Syirkah), Mudharabah or Qiradh, a form of partnership agreement (Syirkah), by: 1. Agreement between the rice field owners and cultivators of rice fields, using mudharabah contracts. 2. Agreement between the paddy field cultivators with the harvesters, or sometimes agreements among the paddy cultivators and rice field harvesters who involve or seek approval from the rice field owners , using mudharabah contracts.